Fatimid Dynasty and Contribution in Education for Islamic Civilization in Egypt (909-1171 AD) - Manggala, Kayan; Syihabuddin, Muhammad; Kholil, Ahmad (Afkaruna: International Journal of Islamic Studies (AIJIS), 2025)
Education plays a crucial role in the development of human civilization, particularly during the Fatimid Dynasty, which ruled from 909 to 1171 AD. This dynasty is renowned for its efforts in establishing educational institutions such as Al-Azhar University, which is considered one of the oldest higher education institutions in the Islamic world and significantly impacted the development of knowledge in Egypt. This study aims to explore the contributions of education during the Fatimid era and its effects on the advancement of knowledge and Islamic culture. The research employs a library study method, allowing the researcher to compile and analyze various documented sources related to education in this period. The findings indicate that the strong support from the Fatimid Dynasty for the advancement of knowledge resulted in the establishment of educational institutions and progress in fields such as philosophy, hadith, fiqh, and linguistics. This research emphasizes the vital role of education in building Islamic civilization and how the educational policies of the Fatimid Dynasty contributed to the widely recognized development of knowledge within the Islamic community.